On Soft β-Open Sets and Soft β-Continuous Functions - Metin Akdag; Alkan Ozkan (The Scientific World Journal)
We introduce the concepts soft β-interior and soft β-closure of a soft set in soft topological spaces. We also study soft β-continuous functions and discuss their relations with soft continuous and other weaker forms of soft continuous functions.